Penilaian keterampilan evaluasi Pendidikan Teori dan Implementasi Melalui Metode Kualitatif - Ina Magdalena; Dimas Andre Odicus; Dina Oktaviani; Maya Iga Nurrahama (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This research was conducted to determine the process of measuring or assessing individual abilities in carrying out certain actions or activities. Skills assessment can be done through various methods, such as tests, observations, interviews, and self-assessments. Skills assessment is very important in education, because it can provide information about students' ability to understand subject matter, as well as assist teachers in determining more effective learning strategies. The function of skills assessment is to measure students' ability to apply knowledge to perform certain tasks in a variety of skill contexts